CHALLENGES AND STRATEGIES FOR CHILD PROTECTION SYSTEM IN EDUCATION: INSIGHTS FROM SOUTHEAST ASIAN COUNTRIES - Chandra Asri Windarsih; Mustofa Kamil; elih sudiapermana; Andika Pratama; Cucu Sukmana (Jurnal Visi Ilmu Pendidikan)
This research aims to explore child protection policies in education in Southeast Asia. Using a Systematic Literature Review (SLR) approach, this research examines policy implementation strategies and the challenges faced. Data sources were obtained from journals indexed in the Scopus and Google Scholar databases with a publication period of 2020-2024, and selection criteria were based on the PRISMA method. The research results show that child protection policies in education require a holistic approach that involves collaboration between government, educational institutions and society. Key findings include the need to strengthen regulations, socio-economic support for families, and safe and inclusive learning environments. The main challenges faced include unequal access to education, lack of resources in remote areas, and weak law enforcement against child exploitation. The original value of this research lies in its focus on Southeast Asia, providing comprehensive insight into the regional context of child protection. Recommendations for future research include developing policies that are more responsive to socio-political dynamics and economic conditions in the region, as well as increasing awareness of the importance of child protection in the digital era.